Escaping the periphery: The East Asian "mystery" solved - Robert H. Wade (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Few non-western countries have reached the general prosperity of Western Europe and North America in the past two centuries. The core-periphery structure of the world economy created in the early decades of the Industrial Revolution has proved robust, even after seven decades of self-conscious "development" following the Second World War. Just about all the countries which were in the periphery in 1960 remain in the periphery today. The clearest exceptions are in capitalist Northeast Asia, namely, Japan, Taiwan, and South Korea; to which the island states of Singapore and Hong Kong might be added. How did they escape?
Keywords: 330; centre; periphery; state capacity; US empire